Transformational leadership and labor satisfaction of the health professional of Aclas Pillco Marca, Huánuco - 2018 - Hancco-Ramos, Danira G. (2019)
The purpose of the study was to determine the type of relationship between transformational leadership and job satisfaction of the health professional of ACLAS Pillco Marca, Huánuco-2018. Methodology: The level of research was relational, prospective, observational, transversal and analytical. The sample population was made up of 65 health professionals. The technique used was the survey and as instruments, two questionnaires. Results: Of the 100% (65) of the health professional who worked at the ACLAS Pillco Marca, Huánuco, during the period from October to December in 2018; 63.1% affirm that if transformational leadership is practiced, of which 56.9% are satisfied with the work they have been doing; However, 36.9% state that transformational Leadership is not practiced, 27.7% are dissatisfied. Considering that the study variable is ordinal, the Chi2 test statistic was chosen, with 1 degree of freedom and 5% of alpha error. The calculated Chi2 was 10,050, (p = 0.000; <0.05), the phi coefficient was = 0.830 (> 0.08), determining a high positive relationship. Conclusion: The general research hypothesis is accepted. Hi: The transformational leadership is significantly related to the job satisfaction of the ACLAS Pillco Marca health professional.